Funções de Autocorrelação e a Taxa de Dissipação da Energia Cinética Turbulenta - Degrazia, G. A.; Gonçalves, J. B.; Welter, G. S.; Maldaner, S.; Timm, A. U.; Acevedo, O. C.; Carvalho, J. C. (Ciência e Natura, 2009)
: